Disciplinary misconduct among secondary school students / Luqman Nurhakim Kasim…[et al.] - Kasim, Luqman Nurhakim; Zuhandri, Nurnisa Athirah; Norismail, Balqis Ameera; Mazelan, Nur Farahani (Faculty of Communication & Media Studies, 2019)
The purpose of this study are to examine the factors, characteristic, and the level of disciplinary misconduct among secondary school students. Based on the research, we want to study the causes of the students misconduct and want to know whether there is the existence of relationships between causes of misconduct and the personality profile of the students. However, the disciplinary problem and misconduct of the students are often a hot topic that discussed by various parties. The study involved 230 respondents, selected through a cluster sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers.